2008
DOI: 10.1016/j.brainres.2008.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hippocampal α1d adrenergic receptor mRNA by corticosterone in adrenalectomized rats

Abstract: The hippocampal formation receives extensive noradrenergic projections and expresses high levels of mineralocorticoid (MR) and glucocorticoid (GR) receptors. Considerable evidence suggests that the noradrenergic system influences hippocampal corticosteroid receptors. However, there is relatively little data describing the influence of glucocorticoids on noradrenergic receptors in the hippocampal formation. α 1d adrenergic receptor (ADR) mRNA is expressed at high levels in the hippocampal formation, within cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…However, both MR (or type I corticosteroid receptor) and GR (or type II corticosteroid receptor) are highly expressed in the hippocampal formation (Reul and de Kloet, 1985; Herman et al , 1989), making this a region that is highly susceptible to changes in circulating glucocorticoids (McEwen, 2007). We have previously reported that expression of α 1d ADR mRNA in the hippocampal formation is dependent on circulating levels of corticosterone, with adrenalectomy resulting in a relatively quick and profound decrease in α 1d ADR mRNA expression in all hippocampal subfields and the dentate gyrus, that was restored with corticosterone replacement (Day et al , 2008). Whether the effect of corticosterone on α 1d ADR mRNA is direct or indirect is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both MR (or type I corticosteroid receptor) and GR (or type II corticosteroid receptor) are highly expressed in the hippocampal formation (Reul and de Kloet, 1985; Herman et al , 1989), making this a region that is highly susceptible to changes in circulating glucocorticoids (McEwen, 2007). We have previously reported that expression of α 1d ADR mRNA in the hippocampal formation is dependent on circulating levels of corticosterone, with adrenalectomy resulting in a relatively quick and profound decrease in α 1d ADR mRNA expression in all hippocampal subfields and the dentate gyrus, that was restored with corticosterone replacement (Day et al , 2008). Whether the effect of corticosterone on α 1d ADR mRNA is direct or indirect is not known.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the possibility that corticosterone could regulate expression of α 1d ADR mRNA after stressor exposure. However, the stress-induced increase in α 1d ADR mRNA was observed only in the dentate gyrus, whereas adrenalectomy resulted in a decrease in α 1d ADR mRNA expression in the dentate gyrus and all hippocampal subfields, which was restored with corticosterone replacement (Day et al , 2008). A similar selectivity of effect has been observed following propagation of cortical spreading depression, with increased alpha 1 adrenergic receptor binding reported in the dentate gyrus, but not the CA1 or CA3 regions of the hippocampus (Haghir et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new reagents and improvements in methods are aimed at increasing the sensitivity, specificity, and quantifying RNA in situ hybridization signals (9). Researchers have many options ranging from the type of backbone of the antisense probe (cDNA, RNA (10), synthetic (11)(12)(13)) to the type of detection label (radioactive (14), chromogenic (15), fluorescent (16)). Approaches such as in situ PCR can be used to amplify the target RNA sequences prior to in situ hybridization.…”
mentioning
confidence: 99%